Concentração plasmática da grelina total, grelina acetilada, leptina, GH e IGF-I em crianças e adolescentes com doença renal crônica - Naufel, Maria Fernanda Soares [UNIFESP] (2009)
Background The mechanisms responsible for the uraemic anorexia are poorly understood. In children and adults with chronic kidney disease (CKD) increased levels of the orexigenic hormone ghrelin are often found. However, no data exits in relationship to concentration of acylated ghrelin in pediatric patients with CKD. Methods Cross-sectional study of acylated and total ghrelin plasma levels in pediatric patients with mild CKD undergoing conservative treatment (MCKD group, n = 19) and patients with end stage renal disease undergoing hemodialysis (ESRD group, n = 24) compared with healthy controls (n =20). The correlations between total or acyl ghrelin with leptin, GH, IGF-I, glomerular filtration rate (GFR) and anthropometric and nutritional measurements were also undertaken. Results ESRD patients had significantly lower BMI Z-score and energy intake while both ESRD and MCKD groups had lower height-for-age Z-score than control group. ESRD patients also exhibited higher total ghrelin levels (2009.7±1278.0 pg/ml, mean±SD) than either MCKD (1117.5±891.9 pg/ml) or controls (655.3±255.6 pg/ml). However, plasma acyl ghrelin levels did not differ between groups. The ESRD group had normal GH but low IGF-I levels. When all 43 uraemic subjects were combined, total ghrelin correlated positively with GH (r =0.340, p=0.0255) and negatively with IGF-I (r= - 0.415, p=0.0057) and GFR (r= -0.534, p<0.0002). Both total and acyl ghrelin correlated negatively with nutritional status. Conclusion The present findings suggest that most of the increased total ghrelin in CKD pediatric patients is desacylated. As desacyl ghrelin has been shown to inhibit feeding, its high levels may contribute to malnutrition and growth deficit in CKD patients.